The joint association of cardiometabolic health and weight on mortality in the multiethnic cohort. Issue 3 (3rd April 2022) - Harmon, Brook E.; Shvetsov, Yurii B.; Lim, Unhee; Leak, Cardella L.; San Diego, Emily Rose N.; Monroe, Kristine R.; Wilkens, Lynne R.; Marchand, Loic Le
ABSTRACT: Objective: While cardiometabolic abnormalities are associated with elevated risk of morbidity, they may not occur in all individuals with obesity. Less is known about associations with mortality, especially cancer mortality. This study examined associations between cardiometabolic-weight categories and mortality from cardiovascular disease (CVD), cancer, and all causes. Methods: Cox proportional hazards regressions of time to all-cause, CVD, and cancer mortalities were used to examine associations with cardiometabolic-weight status, in the Multiethnic Cohort ( n =157, 865). Cardiometabolic-weight status categories were: Metabolically Healthy Normal Weight, Metabolically Healthy Obese, Metabolically Healthy Overweight, Metabolically Unhealthy Normal Weight, Metabolically Unhealthy Obese, and Metabolically Unhealthy Overweight. Results: Higher mortality, especially for all-cause and CVD, was found for all metabolically unhealthy groups no matter the weight classification when compared to the Metabolically Healthy Normal Weight category across sex-ethnic groups. For all-cause mortality, a reduction in mortality was seen for males in the Metabolically Healthy Overweight category (HR: 0.88, 95% CI: 0.84, 0.93), especially for African American, Native Hawaiian, and Latino males. Mortality was elevated in the Metabolically Healthy Obese category for all-cause and CVD mortality in both sexes (HRrange : 1.08–1.93). Few associations were seen with cancer mortality. Conclusions: Past examinations of cardiometabolic-weight status and mortality have been hampered by a lack of diversity. In a racially/ethnically diverse population, metabolically unhealthy groups exhibited a substantially higher risk of death from all causes and CVD than metabolically healthy groups. A reduction in all-cause mortality was seen for some males classified as Metabolically Healthy Overweight; however, being classified as Metabolically Healthy Obese elevated mortality risk for males and females compared to Metabolically Healthy Normal Weight. Future research is needed to examine how sex-ethnic differences in body fat distribution and changes in weight over time influence associations between cardiometabolic-weight status and mortality.